Modelling and Simulation of Zinc-air Flow Battery with Zinc Regeneration Process - Woranunt Lao-atiman; Soorathep Kheawhom (Chemical Engineering Transactions, 2018)
Reliable and low-cost electrical energy storage systems are required for grid integration of various intermittent sources of renewable energy. Zinc-air flow batteries have shown high potential for electricity storage application because of their high energy density at low cost. The flow batteries can reduce significantly the problem associated with the formation of dendritic zinc during recharge and the formation of a passivation film during discharge. The aims of this work include the development of mathematical models of a zinc-air flow battery (ZAFB). The developed model was implemented in MATLAB and validated with experimental data. The models were then used to investigate the behavior of the flow battery. The concentration of potassium hydroxide in the electrolyte, as well as the feed flow rate considerably affected the performance of ZAFB.